Application of stress induces ascorbate peroxidases of S. polyrhiza for green-synthesis Cu nanoparticles - Vipul R. Patel; Nikhil Bhatt (Arabian Journal of Chemistry, 2020)
The objective of this study was to assess the effects of stress on physiology/biochemical component of S. polyrhiza and its impact on CuNPs synthesis and bioethanol production. NaCl with RV5 provokes oxidative stress in S. polyrhiza and significantly increase MAD, Proline, H2O2, ROS, SOD and APX activity compare to control condition. Starch accumulation in S. polyrhiza was found 354% higher and correspond 4.4 times higher ethanol yield under stress condition compare to control. CuNPs were synthesized with an average size of 23–26 nm by purified fraction of APX having 37 KDa MW, 1.44 IU specific activity. Synthesized CuNPs were stable up to 15 consecutive cycles and potency against wide range of reactive dyes. The maximum remedial efficiency of synthesized CuNPs for COD and BOD was 55263.3 ± 3298.5 mg/m3min. and 30560.3 ± 1987.5 mg/m3min. respectively for RV5 wastewater. 0.072 mg/g of bioethanol was produced from the wet pulp remaining after nanoparticles synthesis. High efficiency of CuNPs and significant production of Ethanol, indicate that the feasibility for circular model for continuous industrial wastewater treatment.